Un Abordaje “Indisciplinado” de la Guerra, la Violencia y la Paz en Colombia. Reseña de “Belicopedia” - Hernández Pérez, Mauricio (Ciudad Paz-ando, 2024)
Reseña de: Ruiz, D. y Ojeda, D. (2023). Belicopedia. Universidad de los Andes.